2013
DOI: 10.3233/kes-130267
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cross-domain document clustering with a semantically enhanced text stemmer (SETS)

Abstract: The aim of document clustering is to produce coherent clusters of similar documents. Clustering algorithms rely on text normalisation techniques to represent and cluster documents. Although most document clustering algorithms perform well in specific knowledge domains, processing cross-domain document repositories is still a challenge. This paper attempts to address this challenge. It investigates the performance of the sk-means clustering algorithm across domains, by comparing the cluster coherence produced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The lexical resource used for this purpose is OntoRo. This is an electronic resource based on Roget's Thesaurus [60] and has been employed in several other studies related to design [61] and information retrieval [62], [63]. Moreover, the use of OntoRo is also justified by linguistic studies [36], which have found that many of the names of image schemas correspond to Roget's subcategories.…”
Section: Ontology Of Image Schemasmentioning
confidence: 99%
See 4 more Smart Citations
“…The lexical resource used for this purpose is OntoRo. This is an electronic resource based on Roget's Thesaurus [60] and has been employed in several other studies related to design [61] and information retrieval [62], [63]. Moreover, the use of OntoRo is also justified by linguistic studies [36], which have found that many of the names of image schemas correspond to Roget's subcategories.…”
Section: Ontology Of Image Schemasmentioning
confidence: 99%
“…However, only one of these concepts, #224 interiority, is related to interior as a space enclosed by a boundary, which is the description of container. Even though concept disambiguation using algorithms developed by the authors in previous design studies [61] and information retrieval research [62], [63] is possible, this was considered unnecessary because this procedure is only performed as part of the conceptualization phase of the ontology.…”
Section: Ontology Of Image Schemasmentioning
confidence: 99%
See 3 more Smart Citations